Application of Adaptive UKF Algorithm in Multi-target Tracking and Positioning System - Liu, Guofang; Wang, Xiong (Journal of Applied Data Sciences, 2023)
Adaptive filtering algorithm (FIR) is a design method of adaptive variable target tracking system based on probability density distribution model. The algorithm realizes the target movement in the global range by estimating the parameters of different regions in the image, which improves the real-time performance and effectiveness.